Pengaruh Current Ratio Dan Debt To Asset Ratio Terhadap Kesehatan Perusahaan Pada PT Unilever Indonesia Tbk Periode 2015 – 2024 - Muhammad Imam; Koes Indrakoesoema (PT. Intelek Cendikiawan Nusantara, 2026)
This study aims to examine the effect of Current Ratio and Debt to Asset Ratio on Company Health, measured using Return on Investment (ROI) at PT Unilever Indonesia Tbk during the period 2015–2024. This research employs a quantitative method. The population of this study consists of the financial statements of PT Unilever Indonesia Tbk for the period 2015–2024, while the research sample is derived from the balance sheets and income statements of PT Unilever Indonesia Tbk during the same period. The data analysis techniques used include descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, hypothesis testing (partial t-test and simultaneous F-test), and the coefficient of determination test. The partial test results indicate that the Current Ratio has no significant effect on Company Health (Return on Investment), as evidenced by a t-count value of 1.675 which is lower than the t-table value of 2.776, with a significance value of 0.138 > 0.05. Meanwhile, the Debt to Asset Ratio has a significant and negative effect on Company Health (Return on Investment), indicated by a t-count value of -5.973 which is greater in absolute terms than the t-table value of 2.776, and a significance value of < 0.001 < 0.05. Simultaneously, the results show that the Current Ratio and Debt to Asset Ratio jointly have a significant effect on Company Health (Return on Investment), as indicated by an F-count value of 85.701 which is higher than the F-table value of 4.74, with a significance value of < 0.001 < 0.05. Therefore, it can be concluded that liquidity and solvency ratios simultaneously play an important role in determining the level of company health at PT Unilever Indonesia Tbk